«Sotto l'ombra della patente del Santo Officio» I familiares dell'Inquisizione romana tra XVI e XVII secolo - SOLERA, DENNJ (Premio Tesi di Dottorato, 2019)
What was the Roman Inquisition? How did inquisitors operate in the Italian society of the 16th and 17th century? In an attempt to answer these questions, the author analyses the inquisitors' familia , the Court of Faith's large group of assistants. In the light of rich unpublished records, this research is the first to reconstruct the events around the Holy Office's "staff", which consisted of vicars, notaries, lawyers, consultants, policemen, bodyguards and many others. The publication deals with the issues related to these officers, their geographic distribution and the brotherhoods used for their classification. Following this, the analysis shifts to the privileges enjoyed by the members of these "families", and the often heinous abuses they committed, demonstrating how the Inquisition became an element of social and moral disorder whenever its authority was questioned.